Q&A with Dr Chris O'Connor and Andrew Duncan from DNV GL Oil & Gas - R. G. Jones (The Institute of Materials, Minerals and Mining, 2015)
Many novel projects suffer delays, cost overruns or failure because of inadequately qualified technologies. A new qualification to measure the quality of innovation is discussed.